2001
DOI: 10.1034/j.1600-0765.2001.360301.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bone associated macromolecules by gingival and periodontal ligament fibroblasts

Abstract: The expression of hard tissue associated proteins may be used to identify periodontal fibroblasts with the capability to facilitate periodontal regeneration. The aim of this study was to describe, by immunohistochemistry, the distribution of osteocalcin, osteopontin, bone sialoprotein and bone morphogenic proteins-2 and -4 (BMP-2 and BMP-4) within the human periodontium. Furthermore, the expression of mRNA for the above proteins and alkaline phosphatase by gingival and periodontal ligament fibroblasts in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 27 publications
8
92
0
2
Order By: Relevance
“…Following an examination of previous light-microscopic studies, we have found that studies supporting our findings involve the use of buffered-paraformaldehyde for fixation and EDTA for demineralization (Sasano et al 2001;Ohma et al 2002;Tadatomo et al 2002;Hosoya et al 2003), whereas most other studies employ other chemicals: 95% ethanol (Somerman et al 1990b), Bouin's fixative (MacNeil et al 1994(MacNeil et al , 1995b, and 10% formalin (Ivanovski et al 2001) for fixation; acetic acid (MacNeil et al 1994(MacNeil et al , 1995b and 0.2N HCl (Chen et al 1993;Lekic et al 1996aLekic et al , 1996b for demineralization. Bufferedparaformaldehyde and EDTA are generally recommended for the immunohistochemistry of mineralized tissue, because different chemicals often cause unstable and misleading immunoreactions.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Following an examination of previous light-microscopic studies, we have found that studies supporting our findings involve the use of buffered-paraformaldehyde for fixation and EDTA for demineralization (Sasano et al 2001;Ohma et al 2002;Tadatomo et al 2002;Hosoya et al 2003), whereas most other studies employ other chemicals: 95% ethanol (Somerman et al 1990b), Bouin's fixative (MacNeil et al 1994(MacNeil et al , 1995b, and 10% formalin (Ivanovski et al 2001) for fixation; acetic acid (MacNeil et al 1994(MacNeil et al , 1995b and 0.2N HCl (Chen et al 1993;Lekic et al 1996aLekic et al , 1996b for demineralization. Bufferedparaformaldehyde and EDTA are generally recommended for the immunohistochemistry of mineralized tissue, because different chemicals often cause unstable and misleading immunoreactions.…”
Section: Discussionmentioning
confidence: 51%
“…However, BSP, unlike OPN, is generally considered to be highly specific to mineralized tissues. Other studies have immunodetected BSP only along the root surface in mouse incisors (MacNeil et al 1995a), mouse molars (MacNeil et al 1994, 1995a, 1995b, and dog premolars (Matsuura et al 1995) or have immunodetected no BSP in the periodontal ligament in rat molars (Lekic et al 1996a(Lekic et al , 1996bMatias et al 2003b) or human teeth (Ivanovski et al 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Gingival fibroblasts were found to express variable levels of mRNA for alkaline phosphate and bone morphogenetic protein 2/4 (BMP2/4) in vitro, which demonstrated that appropriate stimuli may direct their capacity of hard tissue formation [8]. By the same token, gingival mesenchymal stem/progenitor cells (GMSCs), with self-renewal capabilities, remarkable differentiation potential, long-term telomerase expression, and outstanding immunomodulatory properties have been isolated [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The periodontal ligament (PDL) for example, a tissue located between the dental roots and the alveolar bone, has osteogenic potential. PDL fibroblasts show Runt-related factor-2 (Runx2; an osteogenic transcription factor) [Jiang et al, 1999] and ALP gene expression both in situ and in vitro [Yamashita et al, 1987;Groeneveld et al, 1996], whereas the osteogenic proteins BSP and osteocalcin are only expressed in vitro [Ivanovski et al, 2001]. Differentiation of PDL fibroblasts into either osteoblasts or cementoblasts in situ occurs depending on the environment [Pitaru et al, 1994].…”
Section: Introductionmentioning
confidence: 99%